2023
DOI: 10.1007/s10597-023-01107-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Implementing the Integrated Behavioral Health Care Model and Iraqi Refugees in the USA

Abstract: The aim was to identify which factors facilitate providing integrated behavioral health care for Iraqi refugees in nationally recognized community health center in Northern USA. The social-ecological model (SEM) framework guided this qualitative case study exploring the experience of 11 professional staff. Data were collected from June through August 2021 through individual interviews. Eight themes emerged based on the SEM levels: Intrapersonal-gender-driven engagement; interpersonal-the need for discretion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Other, less ideal policy options exist. It comprises advocating for integrating behavioral health and primary care services for immigrant populations (Falconer et al, 2018 ; Peer et al, 2023 ). This approach entails central components, including patient-targeted alignment, inclusive and harmonized care, permanent access, and a system-based tactic (Odgkinson et al, 2017 ).…”
Section: Proposed Policy Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other, less ideal policy options exist. It comprises advocating for integrating behavioral health and primary care services for immigrant populations (Falconer et al, 2018 ; Peer et al, 2023 ). This approach entails central components, including patient-targeted alignment, inclusive and harmonized care, permanent access, and a system-based tactic (Odgkinson et al, 2017 ).…”
Section: Proposed Policy Interventionsmentioning
confidence: 99%
“…Researchers have demonstrated that incorporating mental health services into primary care enhances both physical and mental health outcomes, in part because of integrating linguistic services on the provision of care to immigrants with complicated health care issues (Aupont et al, 2013; Kolk et al, 2014). Integration may also help Arab immigrants with severe emotional disturbances reduce their symptoms while enhancing retention and access to care (Odgkinson et al, 2017 ; Peer et al, 2023 ), possibly by reducing the associated stigma via more accessible treatments in a trusted environment (Hodgkinson et al, 2017 ). Evidence from prior literature indicates that that an integrated behavioral care approach has the possibility of promoting engagement with mental health services and maintain care continuity, while decreasing costs of care and stereotyping associated with behavioral healthcare (Falconer et al, 2018 ; Peer et al, 2023 ).…”
Section: Proposed Policy Interventionsmentioning
confidence: 99%
See 2 more Smart Citations